Utilization of Solar Energy As An Environmentally Friendly Source of Electricity In Karang Taruna, Gambir District - Widia Yanti; Reno Pratiwi; Prayang Sunny Yulia; Fadliah Fadliah; Pauhesti Pauhesti; Faiz Rohman; M. Khair Dabit Istibra (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
This community service program titled